The Peruvian Traditions as Ricardo's legacy Palma to Peruvian society - Martos, Marco (2019)
The text refers in a general way to the Peruvian Traditions of Ricardo Palma; and through some examples of them, those referring to Francisco de Carbajal, it infers the idea of Peru that Palma has. His notion of homeland is that of a common ideal in permanent construction which will become better in the future, although it was born in the past. Palma is far from the colonial arcadia, but he is not happy with the republican present that he knew. He has pessimism of the present and the past, but confidence in the future. He was an organic intellectual of Peruvian society.